Strategic Financial and Risk Decisions for Firm Value: Evidence from ASEAN Banks - Mardyaningsih, Wirda (Ekonomis: Journal of Economics and Business, 2026)
This study aims to evaluate the impact of capital structure, credit risk, and strategic risk on the firm value of banks in the ASEAN region, while also examining the role of the Capital Adequacy Ratio (CAR) as a mediating variable. The study employs an explanatory quantitative approach using secondary panel data obtained from the BANKFOCUS database, covering 78 publicly listed banks from eight ASEAN countries over the period 2020–2024, yielding a total of 390 observations. Firm value is measured using Tobin’s Q, capital structure is proxied by the Debt to Asset Ratio (DAR), credit risk by the Non-Performing Loan (NPL) ratio, and strategic risk by BOPO volatility as an indicator of strategic risk. The data analysis was conducted using panel data regression employing the Random Effects model, while the mediating role of CAR is tested using the causal steps approach and the Sobel test. The findings indicate that capital structure and strategic risk have a positive and significant effect on firm value, whereas credit risk exerts a significant negative impact on the firm value of banks in the ASEAN region. Furthermore, capital structure is also found to have a positive and significant effect on the Capital Adequacy Ratio (CAR). The mediation analysis results reveal that the Capital Adequacy Ratio (CAR) has a positive and significant effect on firm value and functions as a partial mediator in the relationship between capital structure, credit risk, and strategic risk and firm value. These results emphasize the critical role of CAR in reinforcing financing strategies and strategic risk management to improve sustainable value of banking firms in the ASEAN region.